Outdoor thermal performance of green roofs across multiple time scales: A case study in subtropical China. (July 2021) - Zheng, Xiandi; Kong, Fanhua; Yin, Haiwei; Middel, Ariane; Liu, Hongqing; Wang, Ding; Sun, Tao; Lensky, Itamar
Highlights: Long-term field measurements were conducted on a full-scale extensive green roof. Outdoor thermal performance was analyzed on daily, seasonal, and annual time scales. Cooling performance corresponds to solar radiation, relative humidity, wind speed, and soil substrate layer. The cooling effect was more pronounced at 60 cm than at 30 cm or 120 cm height. We observed daytime warming and the best cooling effect during hot summers. Abstract: In recent years, roof greening technologies have been developed and implemented worldwide, as green roofs are an effective nature-based solution for alleviating outdoor heat and reducing building energy costs. While most observational green roof studies have investigated the cooling effect of model or test plots, few studies have conducted full-scale measurements; however, to guide green roof implementation, the thermal performance of full-scale roofs is crucial. This experimental study explored the ability of extensive green roofs to reduce outdoor temperatures on multiple time scales. The outdoor cooling effect of green roofs and the main factors that drive its performance were analyzed using long-term observational data collected from May 2016 to April 2019 in Nanjing, China. The results suggest that the cooling effect of green roofs exhibits significant diurnal, seasonal, annual, and vertical trends, and that the cooling performance across different time scales corresponds to weather and soil characteristics. The best cooling effect occurred at a height of 60 cm. The green roof displayed a temporary diurnal warming effect but had a good cooling effect on a seasonal time scale, with the largest amount of cooling occurring during the summer (average of 0.28 °C). The findings of this study can support the development, management, and maintenance of green roofs in subtropical areas.